The Effect of Sharia People's Business Credit (KUR) Financing on the Development of Micro, Small, and Medium Enterprises (MSMEs): A Case Study of PT. Pawnshop CPS Ar Hakim Medan - Yoga Prananda; Alfi Amalia (Universitas KH. Abdul Chalim Mojokerto, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the main pillars of the national economy. Its significant contribution to national GDP, job creation, and economic equity make it a very strategic sector. In addition to contributing to economic growth. This study aims to examine the influence of Sharia People's Business Credit (KUR) financing on the development of Micro, Small, and Medium Enterprises (MSMEs) in PT. CPS AR Hakim Medan Pawnshop. The method applied in this study is a quantitative approach through a survey using a questionnaire distributed to 51 respondents involved in MSMEs. The results of the research that have been carried out show that Sharia KUR financing has a significant impact on increasing revenue, the number of customers, product quality, and the quality of human resources in MSMEs. These findings reinforce the important role of Islamic financial institutions in supporting the sustainable growth of the small business sector.